Hegemon : tracing power through bodies of law - M. Dobber (Law Text Culture, 1995)
'I once had a conversation with a high-ranking member of the CPUSA ... who said that gay people should stay in the closet because it sets a bad example for the 'working class'. ' US gay activist, in conversation: 'The NSW-based Gay and Lesbian Rights Lobby recently knocked back a push by bisexuals and transsexuals to be accepted as part of its overall charter for lobbying ... Those who resisted most strongly were AIDS Council of NSW (ACON) president Peter Grogan, former Mardi Gras president Richard Cobden, gay NSW parliamentary member Paul O'Grady and interim head of the Australian Council for Lesbian and Gay Rights, Carole Ruthchild ... Those against the inclusion ... said that bisexuals could have lovers of the same sex but still resort to the 'safety' net of a heterosexual lifestyle ... The Gay and Lesbian Rights Lobby had earlier expelled Norrie May Welby under the premise that May Welby's constant 'queer' arguments in committee meetings had delayed work on important rights issues.' Campaign 207/June '93